2021
DOI: 10.1186/s12978-020-01062-y
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and misconceptions about contraception and condom use among adolescents in south-east Nigeria

Abstract: Background Misconceptions about the usefulness of condoms and other contraceptives still expose many unmarried adolescents to the risk of unwanted teenage pregnancies and sexually-transmitted infections (STIs). This study explored beliefs and misconceptions about condoms and other contraceptives among adolescents in Ebonyi state, south-east Nigeria. Method A qualitative study was undertaken in six local government areas in Ebonyi state, southeast N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
4
27
0
1
Order By: Relevance
“…It is critical to note that 35 percent of this study participant agrees that condom effectively protects against unplanned pregnancy. This is consistent with the records by Mbachu et al (2021) which revealed mistaken beliefs about methods of preventing pregnancy. These misconceptions will subject unmarried Students to unplanned pregnancies.…”
Section: Discussionsupporting
confidence: 91%
“…It is critical to note that 35 percent of this study participant agrees that condom effectively protects against unplanned pregnancy. This is consistent with the records by Mbachu et al (2021) which revealed mistaken beliefs about methods of preventing pregnancy. These misconceptions will subject unmarried Students to unplanned pregnancies.…”
Section: Discussionsupporting
confidence: 91%
“…In this dimension, they make judgments in relation to their use, on which a negative evaluation is observed, based on their interference with pleasure 10/14 during the sexual act, evidencing that the participants are not satisfied with condom use in their sexual practices. This representation is also a finding in several studies 21,[25][26][27][28] when they associate men with condom use, in which the vast majority think of them as protection, safety and prevention, but refer to the sexual act using the device as something bad, for it interferes with pleasure.…”
Section: /14mentioning
confidence: 67%
“…Our study identified that parents in Nigeria had a significant role to play in the sexual risk behaviors of adolescents: Poor parental oversight, and parental approval of romantic partners increases sexual risk behaviour of adolescents [ 68 , 69 ]. On the other hand, parental connectedness reduces sexual risk behavior for both male and female adolescents, and mother–child communication reduces sexual risk behavior for girls [ 70 ].…”
Section: Discussionmentioning
confidence: 99%